Surgical Aspects of Peritoneal Dialysis - Haggerty, Stephen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book aims to educate general and vascular surgeons on all pertinent aspects of peritoneal dialysis (PD). Most surgeons get very little training in residency on this topic, and the use of PD is growing around the world. Much of the book will focus on implantation techniques, especially laparoscopic insertions. The authors will describe the known adjunct procedures that have been shown to decrease dysfunction rates. The aim is to provide greater patient autonomy, a better quality of life, preservation of residual renal function and a higher survival advantage. .
Physiology of Peritoneal Dialysis -- Laparoscopic Insertion Techniques -- How to perform a correct LI -- Pre-Operative Care -- Post-Operative Care -- How to Avoid Complications -- Catheter Dysfunction -- Assessing and explaining catheter techniques -- Infectious and Mechanical Complications -- How to treat Infections -- Patient Care.
Keywords: Medicine; Radiology; Nephrology; Vascular surgery; Medicine & Public Health; Nephrology; Vascular surgery; Imaging / Radiology